Comparison between PoW and PoS Systems Of Cryptocurrency - Mohammad A. Al Ahmad; Abdullah Al-Saleh; Fahad A. Al Masoud (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Cryptocurrency subject attracted so many people for the last eight years around the globe. Satoshi’s Nakamoto’s, the founder of the bitcoin cryptocurrency behind this revolutionary change in digital money market. Bitcoin cryptocurrency uses “Power of Work” or simply PoW system as its mining algorithm. But in January of 2016, Ethereum cryptocurrency has launched which adopted a new system called “Power of Stake” or simply PoS that is used in Ethereum as its mining algorithm. This paper explores and compares PoW and PoS systems that is used widely today in cryptocurrencies digital money, concluding the pros and cons for each system with enabling to decide which one is more suitable and stable in digital money market.